GENETIC POLYMORPHISMS OF CD14, TNFα AND FCGR2A IN THE PATIENTS WITH INFLUENZA A H1N1 IN TRANSBAIKALIA REGION - V. V. Petrov (SPb RAACI, 2014)
Abstract.  Relative  frequencies  of  CD14  C-159T,  TNFα  G-308A  and  FCGR2A  His166Arg  genetic polymorphisms were studied in the patients with pandemic influenza A H1N1 in Transbaikalia Region. We have revealed that prevalences of allelic TNFα G-308A and CD14 C-159T variants were identical among the patients and in control group. With CD14 C-159T polymorphism, a C allele proved to be associated with severe and complicated clinical course of disease. The [CD14 (159СС); FCGR2A (166Arg/Arg)] haplotype regictered in two cases, was associated with fulminant course and fatal outcomes of the disease. (Med. Immunol.,   2011, vol. 13, N 1, pp 83-86)